Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.